(untitled) (Research, Society and Development, 2025)
This study aimed to analyze the epidemiological profile of urethral discharge in young men aged between 18 and 30 years, treated at outpatient clinics specializing in sexually transmitted infections (STIs). This is a qualitative literature review, carried out based on the analysis of articles published between 2015 and 2025, selected from databases such as SciELO, PubMed, LILACS and Google Scholar. The results indicate a high prevalence of agents such as Chlamydia trachomatis and Neisseria gonorrhoeae, especially among men who have sex with men, associated with risky sexual practices, such as multiple partners, receptive anal sex and inconsistent condom use. The lack of behavioral data in some studies limited a deeper understanding of the context of these young people. It is concluded that there is a need for more effective prevention strategies, focusing on sexual education, expanded testing and qualified support in health services, in order to reduce the transmission of STIs and promote comprehensive care for young men.